ANALYSIS OF FACTORS WHICH AFFECT THE FRAUD OF FINANCIAL STATEMENTS IN BANKING SECTOR COMPANIES REGISTERED IN INDONESIA STOCK EXCHANGE - Hasyim, Liza Widya (International Journal of Public Budgeting, Accounting and Finance, 2019)
This study aims to determine the effect of Return On Assets, Total Receivables Ratio, Total Accrual Ratios, Changes of Directors, and dualism of positions on Financial Statements Fraud in banking sector companies on the Indonesia Stock Exchange. In addition, this study also aims to determine whether the independence of the Audit Committee can be used as a moderating variable in the model. The research design carried out is a causal relationship research with a quantitative approach. The sample in this study was 37 banking companies listed on the Stock Exchange in 2016 to 2018. The type of data used in this study is secondary data. And data analysis techniques using multiple linear regression analysis and interaction testing (moderating) conducted with the help of Eviews software. The results in this study indicate that partially Return On Assets, Total Accrual Ratio and Changes of Directors have a positive and significant effect on Financial Statement Fraud. As well as other results which show that the Audit Committee Independence is not a moderating variable in the influence of Return On Assets, total receivables ratio, Changes of Directors, Total Accruals Ratio, and dualism of positions on Financial Statement Fraud on banking sector companies on the Indonesia Stock Exchange.